2001
DOI: 10.1291/hypres.24.481
|View full text |Cite
|
Sign up to set email alerts
|

Association between Blood Pressure and Insulin Resistance in Obese Females during Weight Loss and Weight Rebound Phenomenon.

Abstract: The purpose of this study was to investigate the effect of weight loss on blood pressure and its related variables in moderately obese Japanese females, including an investigation of the rebound phenomenon. Study I examined the effects of weight loss on blood pressure in 138 moderately obese, nondiabetic females (BMI 29.3+/-0.3 kg/M2; age, 46.3+/-0.8 years) during a 3-month therapeutic dietary and exercise program. Study II investigated the effect of weight rebound on blood pressure over an additional 21 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…In a study by Eriksson et al, the complications of impaired glucose tolerance or diabetes mellitus, hyperinsulinemia, and hypertriglyceridemia were found in 6% of all hypertensives, or twice as frequently as in the normotensive population (12). Itoh et al reported that weight reduction during a 3-month therapeutic dietary and exercise program was significantly and positively associated with BP reduction and improvement of hyperinsulinemia (40). The present study also suggests that the complication of metabolic disturbances increases the risk for BP elevation.…”
Section: Discussionsupporting
confidence: 70%
“…In a study by Eriksson et al, the complications of impaired glucose tolerance or diabetes mellitus, hyperinsulinemia, and hypertriglyceridemia were found in 6% of all hypertensives, or twice as frequently as in the normotensive population (12). Itoh et al reported that weight reduction during a 3-month therapeutic dietary and exercise program was significantly and positively associated with BP reduction and improvement of hyperinsulinemia (40). The present study also suggests that the complication of metabolic disturbances increases the risk for BP elevation.…”
Section: Discussionsupporting
confidence: 70%
“…Seven studies included female participants only Itoh et al 2001;Kuller et al 2006Kuller et al , 2007Kuller et al , 2012Matsuo et al 2010;Rock et al 2007;Teixeira et al 2010;West et al 2011;Wing et al 2010;Yankura et al 2008). Again, these studies found levels of weight loss and weight maintenance similar to those found in studies with both males and females (5%-10%), with the exception of 1 study ) that found ϳ12% lower weight after the weight-loss phase and ϳ9% lower weight from baseline at the end of the maintenance phase.…”
Section: Sexsupporting
confidence: 56%
“…For 7 of these studies, the percentage of weight loss could not be calculated, but a significant absolute weight loss-weight maintenance was reported Itoh et al 2001;Jeffery et al 2009;Kuller et al 2006Kuller et al , 2007Kuller et al , 2012Leermakers et al 1999;Tanumihardjo et al 2009;Wolfson et al 2010;Yankura et al 2008;Yatsuya et al 2011) and thus, these studies were retained. The majority of retained studies (n = 20) reported that participant weight was measured by study staff.…”
Section: Weight-loss and Weight-maintenance Combined Studies (N = 24)mentioning
confidence: 99%
See 2 more Smart Citations